PERUBAHAN KOMPOSISI KOMUNITAS IKAN DAN FAKTOR-FAKTOR PENTING YANG MEMENGARUHI SELAMA EMPAT PULUH TAHUN UMUR WADUK DJUANDA [Change of Fish Community Composition and The Influencing Important Factors During Fourty Years of The Djuanda Reservoir Impounded] - Endi Setiadi Kartamihardja (Jurnal Iktiologi Indonesia, 2008)
Ecologically, damming of Citarum River have altered running waters ecosystem to become impounded ecosystem, Djuanda reservoir. Studies concerning change of fish community composition and important factors which influence them have been conducted in the Djuanda reservoir after 40 years the reservoir completed. Primary data of fish composition were obtained from experimental gillnet sampling of various mesh sizes which compiled in one fleet net, while secondary data were obtained from the literature study. Data analysis and evaluation was conducted based on 4 periods of 10 years since flooding of the reservoir i.e. 1968-1977, 1978-1987, 1988-1997, and 1998-2007. Important ecological factors such as loss of spawning and nursery habitat, degradation of water quality and water level fluctuation of the reservoir have influenced the indigenous fish species of the Citarum River. Fish composition has changed in number as well as in comparison between the indigenous species (23 species) and the exotic species (11 species). Total number of fish species decreased from 34 species to 20 species, while comparison between the indigenous species and exotic species changed from 23:8 to 9:11. Some indigenous species such as carp (Tor duoronensis), java barb (Barbodes gonionotus), lalawatc barb (Barbodes bramaides), genggehek (Mystacoleucus marginalus), jambal catfish (Pangasius djambai), Arengan (Labeo chrysophaekadion), eel (Anguilla sp.) and feather back (Notoplerus chitala) disappeared due to their riverine species need running water habitat and relatively high dissolved oxygen content.